2020
DOI: 10.1155/2020/6384530
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Fire Retardancy of Bis(1‐methoxy‐2,2,6,6‐tetramethylpiperidin‐4‐yl)sebacate and Tris(2,4,6‐tribromophenoxy)‐1,3,5‐triazine/Sb2O3 in HIPS

Abstract: Bis(1-methoxy-2,2,6,6-tetramethylpiperidin-4-yl)sebacate (NORSM) was found to perform an exceptional synergistic effect with tris(2,4,6-tribromophenoxy)-1,3,5-triazine (TTBPC)/Sb2O3 in HIPS. The LOI of fire retardant HIPS (FR-HIPS) with 16 wt% of TTBPC/Sb2O3 increased from 23.8% to 25.2%, the flame retardant rating of FR-HIPS was improved from UL 94 V-2 to UL 94 V-0, and various heat release parameters such as peak heat release rate, total heat release, and mean effective heat of combustion were greatly lowere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…The above‐mentioned analysis of the pyrolysis products shows that NORSM imparts the synergistic effect mainly through the following mechanisms: active radicals such as methyl radicals, methoxy radicals, nitro radicals and aminyl radicals produced by the pyrolysis of NORSM, 20 but methoxy radicals and aminyl radicals might be the most important species for interrupting the free radical reactions during the polymer combustion process, 36 together with PH 3 and HBr, quench active free radical such as hydroxyl radical (·OH), thus the chain reaction of combustion is interrupted, which results in more highly efficient flame retardant effect in gaseous phase 37,38 . However, it has been well established that alkoxy radicals can promote chain scission of polypropylene, 39 thereby accelerating the breakdown of polypropylene during combustion, 19 which is beneficial to burning of PP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The above‐mentioned analysis of the pyrolysis products shows that NORSM imparts the synergistic effect mainly through the following mechanisms: active radicals such as methyl radicals, methoxy radicals, nitro radicals and aminyl radicals produced by the pyrolysis of NORSM, 20 but methoxy radicals and aminyl radicals might be the most important species for interrupting the free radical reactions during the polymer combustion process, 36 together with PH 3 and HBr, quench active free radical such as hydroxyl radical (·OH), thus the chain reaction of combustion is interrupted, which results in more highly efficient flame retardant effect in gaseous phase 37,38 . However, it has been well established that alkoxy radicals can promote chain scission of polypropylene, 39 thereby accelerating the breakdown of polypropylene during combustion, 19 which is beneficial to burning of PP.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, all materials were used as received. NORSM was prepared according to the process described in the literature 29 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] It was also found that bis(1-methoxy-2,2,6,6-tetramethyl-4piperidinyl)sebacate performed an exceptional fire retardant synergy with tri(tribromophenyl) cyanurate/Sb 2 O 3 in high impact polystyrene. [15] In addition, NORSs have some merits such as simple molecular structure and preparation process as well as good heat resistance and anti-migration ability. [16][17][18][19] Some other NORs also exhibit good fire retardancy in PP.…”
Section: Introductionmentioning
confidence: 99%